Suitability of bio-extracts with coating materials on physicochemical quality of tomato fruits (Solanum Lycopersicum L.) stored at ambient temperature - Desta Dugassa Fufa (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Tomato (Solanum Lycopersicum L. (or) Lycopersicon esculentum Mill.) is being a very nutritious and health protective food, are highly perishable nature. Its sensitivity to postharvest loss due to poor handling, diseases and physical injury limits its successful marketing. Therefore, simple technology is required to reduce the postharvest loss of this commodity. The use of edible coatings with bio-extracts appears to be a good alternative preservation technique to extend the mature tomato fruits. This study was, therefore, initiated to investigate the effect of using bio- extracts garlic bulba and capsicum incorporation with coating materials (maize starch and beeswax on physicochemical quality of tomato fruit stored at ambient conditions (temperature 15.5 to 20.2oC and relative humidity of 55.5 to 67.3%). The experiment was conducted using complete randomized design of two varieties (Fetane and Melkashola) and six treatments. The tomato fruits were coated by dipping into solution for 3 minutes. The treatments prepared were on coating solution of MGE( 9.5% maize starch with 0.5% garlic extract), MCE (9.5% maize starch with 0.5% capsicum extract), BCE (9.5% beewax mixed with 0.5% capsicum extract), BGE (9.5% beewax mixed with 0.5% garlic extract), 10% maize starch without bio-extract, 10% beewax without bio- extract and control. The treatment means were tested at significance level of P ≤ 0.05. The effectiveness of bio-extracts with coating materials on physicochemical quality of tomato fruits were evaluated at three days intervals for 30 days. There was a significance difference (P<0.05) between coated and uncoated fruits. All coatings delayed tomato ripening and improved the keeping quality parameters but best results were exhibited by 9.5% with 0.5% BCE followed by 9.5% with 0.5% MGE by maintaining the mature tomato fruit for 30 days. The study showed that the Fetane variety has maintained more quality attribute than Melkashola variety during storage.